But how are you, really : a novel - Dawson, Ella 1992- ([New York] : Dutton, an imprint of Penguin Random House LLC, 2024)
"Sex and culture critic Ella Dawson's But How Are You, Really, about a burned-out bisexual young woman who attends her five-year college reunion and confronts her estranged chosen family, old demons, and the ex she maybe shouldn't have walked away from. But How Are You, Really is equal parts sexy second chance romance, a powerful reckoning with toxic workplace culture and burnout, and an exploration of surviving emotional abuse and what it means to get unstuck, in both love and in life, with the help of your community. Charlotte Thorne does not want to go back to Hein University. Her life post college is hardly what she dreamed-her career in media is stalled, her passion for drawing has fallen by the wayside, and she wishes she was better at keeping in touch with her college friends, including her best friend and former roommate, Jackie. Willingly spend a full weekend with her incredibly successful classmates? Hard pass. But when her toxic, controlling boss, tech journalist Roger Ludermore, is invited to give the commencement address at this year's graduation-which also happens to fall on the same weekend as her five year reunion-Charlotte has no choice but to return to campus. The minute she steps foot on Hein property, the past comes crawling back in its glory and cringe: her chemistry with Reece Kreuger, the hockey player she rebounded with after a traumatic breakup, sleeping in a twin bed, and the thrill of getting ready to go out dancing with your best friends. Suddenly the weekend Charlotte has dreaded for months feels like an opportunity to go back in time. Determined to have some fun, Charlotte dodges Jackie's questions about her mental health, tries to avoid confronting the truth about why she ghosted Reece on graduation day five years ago, and ignores her boss's constant Slack messages as his arrival on campus looms large. But can she really outrun her past and reckon with a hopeful version of herself in seventy-two hours?"--
Keywords: Romance fiction; Bisexual fiction; Novels